Pemeliharaan dan Pemuliharaan Alam Sekitar di Malaysia - Rahman, Haliza Abdul (PENERBIT USM, 2015)
This book consists of 12 chapters contributed by authors of various areas of knowledge in their response to the importance of preservation and conservation of nature in Malaysia. This book was written to provide knowledge, information and awareness of issues pertaining to nature preservation and conservation in Malaysia to promote its continuance. This is because environmental issues are increasingly important and apparent in daily life and are the main agenda in the country's development. It is important to preserve and conserve nature as it has much to offer mankind and it is also a priceless life support system. It is hoped this book can fill the gap not covered by other books while fostering a caring attitude and deep love for nature.